The costs of taxation in the presence of inequality - Åsmund Sunde Valseth; Bjart Holtsmark; Katinka Holtsmark (Statistics Norway, Research Department, 2019)
This paper provides a new and improved measure of the marginal cost of public funds (MCF). It is based on a benchmark tax which is distributionally neutral and non-distortive. This is in contrast to the MCF-measure used in the previous literature, that has used the regressive uniform lump-sum tax as the benchmark. Our proposed MCF-measure more precisely accounts for the distributional aspects of public funding (the tax scheme) and makes a clear distinction between this and the distributional aspects of the public good considered. Compared to the previous literature, we find a higher MCF both in the case of a uniform lump-sum tax and in the case of distortive taxes. Due to its regressive distributional consequences, we find that the MCF of a uniform lump-sum tax is always greater than one when not combined with distortive taxes. Moreover, we find that the MCF could be greater than one also with an optimal combination of a uniform lump-sum tax and distortive taxes.
Keywords: H20; H40; H50; 330; Marginal cost of public funds; lump-sum taxes; public goods